24 Hours Urinary Hydroxyproline - A Noninvasive, Cost-Effective and Early Biochemical Marker Which May be Used to Screen the Osteoporotic Lesion in Postmenopausal Women - Das, Mousumi; Biswas, Utpal Kumar; Kumar, Arun (Asian Journal of Medical Sciences, 2015)
Introduction: Osteoporosis results due increased rate of bone turnover. It has multifactorial etiology and most common in women after menopause. Objective: The current study was aimed to assess the rate of bone turnover towards detection of osteoporotic changes by measuring 24 hours urinary hydroxyproline which is an early as well as non- invasive biochemical bone marker. Methods: Urinary hydroxyproline was measured in 40 postmenopausal women and compared with similar number of premenopausal women as controls. Results: 24 hours urinary hydroxyproline levels were significantly higher (p<0.001) in postmenopausal women than premenopausal groups. This indicates a higher rate of bone turnover suggesting osteoporotic changes. 24 hour urinary hydroxyproline is also positively correlated (r= 0.934) with age. Conclusion: The present study suggests that measurement of 24 hours urinary hydroxyproline which is a cost-effective and non- invasive technique, may be used for screening and early detection of osteoporotic changes in women of postmenopausal age group. DOI: http://dx.doi.org/10.3126/ajms.v6i4.11853 Asian Journal of Medical Sciences Vol.6(4) 2015 21-24